Terrorism and counter-terrorism in modern sub-Saharan Africa - Besenyő, János; Khanyile, Moses B.; Vogel, David (African histories and modernities, 2024)
Acts of terrorism and forms of counter-terrorism have been evolving for quite a long time. Although we have been living with these phenomena for centuries, they have only recently become part of the daily lives of many in the West since the dawn of the millennium. In some countries, they have become so prevalent that they shape the daily lives and habits of citizens. For these reasons, it is of utmost importance for all of us to understand the root causes, the drives and the motives behind terrorist activities, preferably even before they can materialize. In this challenge, counter-terrorism activities play a crucial role. In this book, contributors from various disciplines discuss terrorism and counter-terrorism on the African continent through case studies from Nigeria, Kenya, Cameroon, Ghana, or Mozambique and the Sahel region. In addition to analysis, they offer possible steps for improving the situation. János Besenyő is Full Professor at the Doctoral School on Safety and Security Sciences at Óbuda University, Hungary and Head of the Africa Research Institute. Moses B. Khanyile is Director of the Center for Military Studies and the Faculty of Miltary Science at Stellenbosch University, South Africa. David Vogel is Senior Research Fellow and founding member and Deputy Head of the Africa Research Institute of the Doctoral School on Safety and Security Sciences at Óbuda University, Hungary.